Pentingnya Peran Keluarga dalam Melestarikan Bahasa Daerah kepada Anak di Zaman Modern (Studi pada Masyarakat di Kota Medan) - Hutagalung, Siti Nur Ibni Aulia; Sutarini, Sutarini (Lembaga Yasin AlSys, 2025)
This study is motivated by the marginalization of regional languages, largely driven by the influence of social media, education, and entertainment, factors that have become major contributors to language shift. Medan, as a multicultural metropolitan city, faces similar challenges. The aim of this research is to prevent further shifts in regional language, literature, and script, which could significantly impact cultural preservation, as language is closely intertwined with culture. A qualitative approach was employed, utilizing interviews and observations with several families in Medan. The findings reveal that the family holds a strategic position as the primary and most influential agent in the transmission of regional languages. The role of families in preserving regional languages among children in the modern era is crucial. By actively using the regional language, introducing local wisdom, and instilling cultural values, families can maintain children’s cultural identity and help preserve regional cultural heritage. The study in Medan shows that families or parents who actively use regional languages in daily communication and instill local cultural values make a significant contribution to the language’s continued existence. Conversely, when children are not exposed to their regional language and culture in everyday life, the language faces the risk of extinction. This research highlights the importance of family awareness and commitment to continuously use and teach regional languages as part of a cultural legacy that must be preserved and passed on to future generations.